Investigation of Purchase Decisions Based on Product Features offered - Iskamto, Dedi (ADPEBI International Journal of Business and Social Science, 2021)
This study aims to determine the relationship between the influence of the product in terms of product form, product quality, product type, product utilization, and product durability. This research is a quantitative study where the research data processing uses SPSS 26. Found a low average value on information search indicators and post purchase behaviour, while the highest average value is found in the needs recognition indicator. In the product variable, the lowest average indicator is in the product form, while the product type has the highest average value. The regression equation test shows that the effect of the Product Features variable on the purchasing decision variable is positive and significant.